High-Throughput Mass Spectrometric Analysis of Covalent Protein-Inhibitor Adducts for the Discovery of Irreversible Inhibitors: A Complete Workflow. (February 2016) - Campuzano, Iain D. G.; San Miguel, Tisha; Rowe, Todd; Onea, Daniel; Cee, Victor J.; Arvedson, Tara; McCarter, John D.
We have implemented a solid-phase extraction based time-of-flight mass spectrometer system in combination with novel informatics to rapidly screen and characterize the covalent binding of different irreversible inhibitors to intact proteins. This high-throughput screening platform can be used to accurately detect and quantitate the extent of formation of different covalent protein-inhibitor adducts between electrophilic inhibitors and nucleophilic residues such as cysteine or lysine. For a representative 19.5 kDa protein, the analysis time is approximately 20 s per sample, including an efficient sample loading and desalting step. Accurate protein masses are measured (±0.5 amu of the theoretical molecular weight; measured precision of ±0.02 amu). The fraction of protein reacted with an electrophilic compound is determined relative to an unmodified protein control. A key element of the workflow is the automated identification and quantitation of the expected masses of covalent protein-inhibitor adducts using a custom routine that obviates the need to manually inspect each individual spectrum. Parallel screens were performed on a library of approximately 1000 acrylamide containing compounds (different structures and reactivities) using the solid-phase extraction mass spectrometry based assay and a fluorescence based thiol-reactive probe assay enabling comparison of false positives and false negatives between these orthogonal screening approaches.